Large genomic differences between Moraxella bovoculi isolates acquired from the eyes of cattle with infectious bovine keratoconjunctivitis versus the deep nasopharynx of asymptomatic cattle - Dickey, A. M.; Loy, J. D.; Bono, J. L.; Smith, T. P. L.; Apley, Michael D.; Lubbers, Brian V.; DeDonder, K. D.; Capik, S. F.; Larson, Robert L.; White, Bradley J.; Blom, J.; Chitko-McKown, C. G.; et al. (My University, 2016)
Moraxella bovoculi is a recently described bacterium that is associated with infectious bovine keratoconjunctivitis (IBK) or "pinkeye" in cattle. In this study, closed circularized genomes were generated for seven M. bovoculi isolates: three that originated from the eyes of clinical IBK bovine cases and four from the deep nasopharynx of asymptomatic cattle. Isolates that originated from the eyes of IBK cases profoundly differed from those that originated from the nasopharynx of asymptomatic cattle in genome structure, gene content and polymorphism diversity and consequently placed into two distinct phylogenetic groups. These results suggest that there are genetically distinct strains of M. bovoculi that may not associate with IBK.
Citation: Dickey, A. M., Loy, J. D., Bono, J. L., Smith, T. P. L., Apley, M. D., Lubbers, B. V., . . . Clawson, M. L. (2016). Large genomic differences between Moraxella bovoculi isolates acquired from the eyes of cattle with infectious bovine keratoconjunctivitis versus the deep nasopharynx of asymptomatic cattle. Veterinary Research, 47, 11. doi:10.1186/s13567-016-0316-2
Keywords: Sp-Nov; Strains; Calves; Vaccine; Identification; Phylogenies